Spatial Control of Substitutional Dopants in Hexagonal Monolayer WS2: The Effect of Edge Termination (Small 6/2023). Issue 6 (8th February 2023) - Zhang, Tianyi; Liu, Mingzu; Fujisawa, Kazunori; Lucking, Michael; Beach, Kory; Zhang, Fu; Shanmugasundaram, Maruda; Krayev, Andrey; Murray, William; Lei, Yu; Yu, Zhuohang; Sanchez, David; et al.
Abstract : The Effect of Edge Termination In article number 2205800, Humberto Terrones, Ana Laura Elías, Mauricio Terrones, and co‐workers demonstrate the importance of atomic edge termination in determining the spatial distribution of substitutional dopants in 2D transition metal dichalcogenide (TMD) hexagonal monolayers. Preferential iron and vanadium doping occurs on the sulfur‐terminated edges of the hexagonal monolayers, causing a decrease in photoluminescence intensity and forming binary optical/electrical domains.